The Genitourinary Pathology Society Update on Classification and Grading of Flat and Papillary Urothelial Neoplasia With New Reporting Recommendations and Approach to Lesions With Mixed and Early Patterns of Neoplasia. (July 2021) - Amin, Mahul B.; Comperat, Eva; Epstein, Jonathan I.; True, Lawrence D.; Hansel, Donna; Paner, Gladell P.; Al-Ahmadie, Hikmat; Baydar, Dilek; Bivalacqua, Trinity; Brimo, Fadi; Cheng, Liang; Cheville, John; et al.
Abstract : The Genitourinary Pathology Society (GUPS) undertook a critical review of the recent advances in bladder neoplasia with a focus on issues relevant to the practicing surgical pathologist for the understanding and effective reporting of bladder cancer, emphasizing particularly on the newly accumulated evidence post-2016 World Health Organization (WHO) classification. The work is presented in 2 manuscripts. Here, in the first, we revisit the nomenclature and classification system used for grading flat and papillary urothelial lesions centering on clinical relevance, and on dilemmas related to application in routine reporting. As patients of noninvasive bladder cancer frequently undergo cystoscopy and biopsy in their typically prolonged clinical course and for surveillance of disease, we discuss morphologies presented in these scenarios which may not have readily applicable diagnostic terms in the WHO classification. The topic of inverted patterns in urothelial neoplasia, particularly when prominent or exclusive, and beyond inverted papilloma has not been addressed formally in the WHO classification. Herein we provide a through review and suggest guidelines for when and how to report such lesions. In promulgating these GUPS recommendations, we aim to provide clarity on the clinical application of these not so uncommon diagnostically challenging situations encountered in routine practice, while also importantly advocating consistent terminology which would inform future work.